Instructional communication scholarship: Complementing communication pedagogy - Goodboy, Alan (Journal of communication pedagogy (Print), 2018)
Instructional communication "refers to the study of the human communication process across all learning situations independent of the subject matter, the grade level, or the learning environment" (Myers, Tindage, and Atkinson, 2016, p. 13). Accordingly, much of instructional communication scholarship is generalizable, providing pedagogical findings about "communication variables, strategies, processes, technologies, and/or systems as they relate to formal instruction and the acquisition and modification of learning outcomes" which are "applicable to many disciplines, educational levels, and environments" (Lashbrook and Wheeless, 1979, p. 439). Although instructional communication scholars historically have examined effective teaching behaviors that foster student affective, behavioral, and cognitive learning (Hurt, Scott, and McCroskey, 1978), they also study communication processes in the classroom (see Witt, 2016), which include instructor characteristics and actions (e.g., how instructors effectively provide written or oral feedback to students), student characteristics and attitudes (e.g., how students' communication apprehension affects their group work), pedagogy and classroom management (e.g., how classroom technology policies encourage student engagement), and developmental communication across the lifespan (e.g., how children and adult learners benefit from communication training programs). More recent instructional scholarship has continued to examine effective teaching behaviors (Conley and Ah Yun, 2017), but with a greater focus on understanding student communication behaviors in the classroom (Mazer and Graham, 2015).